Effect of selective cyclooxygenase-2 inhibition on the development of ligature-induced periodontitis in rats - Holzhausen, M.; Rossa, C.; Marcantonio, E.; Nassar, P. O.; Spolidório, Denise Madalena Palomari [UNESP]; Spolidório, Luis Carlos [UNESP] (Amer Acad Periodontology, 2002)
Background: the purpose of this study was to evaluate the effect of a selective cyclooxygenase-2 inhibitor on the progression of alveolar bone loss in an experimental periodontitis model in rats.Methods: One hundred eighty (180) Wistar rats were separated into 3 experimental groups. Cotton ligatures were placed at the gingival margin level of lower right first molars. The rats were randomly assigned to one of the following groups that received: a daily oral dose of 10 mg/kg body weight of celecoxib (Ce1); 20 mg/kg body weight of celecoxib (Ce2); or 10 ml/kg of saline solution (C). Serum levels of celecoxib and white blood cell count were determined. Standardized digital radiographs were taken after sacrifice at 3, 5, 10, 18, and 30 days to measure the amount of bone loss around the mesial root surface of the first molar tooth in each rat.Results: Two-way analysis of variance (ANOVA) indicated that groups treated with celecoxib had significantly less bone loss compared to controls (P <0.0001) and that there was a significant interaction between treatment with celecoxib and time (P <0.03). Post-hoc comparisons showed that in both groups treated with celecoxib, the bone loss became significant only after 10 days of ligature placement, while in the control group it was already significant after 5 days. However, differences in mean bone loss between control and Ce1 were significant only at 18 days and, between control and Ce2, at 5 and 18 days. There was no significant difference in bone loss among experimental groups at the end of the experimental period.Conclusion: These data provide evidence that systemic therapy with celecoxib can modify the progression of experimentally induced periodontitis in rats.
Keywords: alveolar bone loss/prevention and control; cyclooxygenase inhibitors; animal studies; periodontitis/prevention and control